2002
DOI: 10.1029/2001ja000254
|View full text |Cite
|
Sign up to set email alerts
|

FAST observations of discrete electrostatic waves in association with down‐going ion beams in the auroral zone

Abstract: [1] Ion beams flowing downward, into the ionosphere, along the Earth's magnetic field have frequently been observed by the FAST satellite in the auroral zone. These discrete downward moving ion beams (DFI) have been characterized by Klumpar et al. [1999] who interpreted the horseshoe-shaped distributions as being consistent with acceleration in a parallel potential drop above the satellite, followed by motion into a region of increased magnetic field strength. The down-flowing ion beams are associated with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 28 publications
4
21
0
Order By: Relevance
“…. 3,8,24,25 Depending on the velocity distribution assumed, various authors have discussed ion cyclotron harmonic instability that can be generated by beams, 26 loss-cone, 27 or subtracted Maxwellian distributions, 8 although it should be noted that in some cases, authors refer to the modes as being ion Bernstein waves, even though k k =k ? is small but non-zero.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…. 3,8,24,25 Depending on the velocity distribution assumed, various authors have discussed ion cyclotron harmonic instability that can be generated by beams, 26 loss-cone, 27 or subtracted Maxwellian distributions, 8 although it should be noted that in some cases, authors refer to the modes as being ion Bernstein waves, even though k k =k ? is small but non-zero.…”
Section: Introductionmentioning
confidence: 98%
“…[1][2][3][4] In many cases, their detection is confined to a rather small angular wedge, centred on the geomagnetic equator, 1,2 suggestive of propagation perpendicular (or nearly perpendicular) to the ambient magnetic field. The fact that their frequency structure is governed by the ion gyrofrequency and its harmonics and that they propagate perpendicularly to the magnetic field make the ion Bernstein 5 wave a strong candidate for the production of these waves.…”
Section: Introductionmentioning
confidence: 99%
“…Bouhram et al, 2003). Ion beams (Cattell et al, 2002), temperature anisotropy (André et al, 1986) and velocity shears (Lakhina, 1990) are plasma instabilities commonly observed. Bernstein modes and Alfvén modes obviously interact with particles in this region (Kintner et al, 1986;Chaston et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Cattel et al, 2002, Mozer et al, 1997, Ergun et al, 1998, and Pickett et al, 2003, Dubinin et al, 2007 has stimulated the development of theoretical models to explain the observations based on travelling waves in multi-fluid plasmas (e.g. Sauer et al, 2001, Verheest et al, 2004, Webb et al, 2005, Dubinin et al, 2007.…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%